Pengaruh Profitabilitas, Struktur Aset, Ukuran Perusahaan dan Kebijakan Dividen Terhadap Kebijakan Utang (Studi Kasus Pada Perusahaan Asuransi Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2016-2021) - Annisa Raylia Putri; Agung Nurmansyah; Annisa Indah mutiasari (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
This study examines the effect of profitability, asset structure, company area, and dividend policy variables on debt policy. This study used a sample of 14 insurance companies listed on the Indonesia Stock Exchange during 2016-2021. It was explanatory research using a quantitative approach. The sampling method used purposive sampling. The results indicate that the variables of profitability, asset structure, company area, and dividend policy simultaneously affect debt policy. Profitability, asset structure, and dividend policy partially have a significant effect on debt policy. While the company area partially does not have a significant impact on debt policy. The most dominant variable influencing debt policy is the asset structure variable.